Neurodegenerative Disease Phenotypes in Carriers of MAPT p.A152T, A Risk Factor for Frontotemporal Dementia Spectrum Disorders and Alzheimer Disease - Lee, Suzee E.; Tartaglia, Maria C.; Yener, Görsev; Genç, Sermin; Seeley, William W.; Sanchez-Juan, Pascual; Moreno, Fermin; Mendez, Mario F.; Klein, Eric; Rademakers, Rosa; Lopez de Munain, Adolfo; Combarros, Onofre; et al. (Lippincott Williams & Wilkins, 530 Walnut St, Philadelphia, Pa 19106-3621 USA, 2013)
Recently, Coppola and colleagues demonstrated that a rare microtubule-associated protein tau (MAPT) sequence variant, c.454G>A (p.A152T) significantly increases the risk of frontotemporal dementia (FTD) spectrum disorders and Alzheimer disease (AD) in a screen of 15,369 subjects. We describe clinical features of 9 patients with neurodegenerative disease (4 women) harboring p.A152T, aged 51 to 79 years at symptom onset. Seven developed FTD spectrum clinical syndromes, including progressive supranuclear palsy syndrome (n=2), behavioral variant FTD (bvFTD, n=1), nonfluent variant primary progressive aphasia (nfvPPA, n=2), and corticobasal syndrome (n=2); 2 patients were diagnosed with clinical AD. Thus, MAPT p.A152T is associated with a variety of FTD spectrum clinical presentations, although patients with clinical AD are also identified. These data warrant larger studies with clinicopathologic correlation to elucidate the influence of this genetic variant on neurodegenerative disease.
Keywords: all cognitive disorders; dementia; Alzheimer disease; frontotemporal dementia; corticobasal degeneration; progressive supranuclear palsy; tüm bilişsel bozukluklar; bunaklık; Alzheimer hastalığı; frontotemporal demans; kortiküsobazal dejenerasyon; ilerleyici supranüklear felç